Eco-toxicity of water, soil, and sediment from agricultural areas of Kilombero Valley Ramsar wetlands, Tanzania - S. F. Materu (Taylor & Francis Group, 2019)
This study was conducted in the KVRS to; evaluate the seasonal eco-toxicity of water, soil and sediment samples; establish the suitability of using temperate biotest batteries in tropical systems; classify the toxicity of samples using Fuzzy Rules to estimate potential ecological risks. 143 water, sediment, and soil samples were collected during dry and rainy seasons in plantation areas. Pseudokirchneriella subcapitata, Aliivibrio fischeri and Arthrobacter globiformis bioassays were used to assess the toxicity of the samples. Results were categorized and classified into toxicity classes. Dry season presented a significantly higher mean inhibition of 31% than 5% shown by rainy season samples (p < 0.001) in the bacterial bioassays, indicating a lower concentration of contaminants due to flooding and increased surface runoff. A few sediment samples resulted into 100% inhibition of A. globiformis, implying organisms were physiologically inactive upon exposure to contaminants. Seventy-three percent of samples posed little or no toxic potential risk, 25% posed critical risk and 1% posed elevated critical risk, implying the KVRS ecosystem might be at risk if the extensive usage of pesticides in the area is not well managed and monitored. The temperate micro-biotests can be used in tropical systems, but with further research on suitable organisms and standardized methods.